IMPLEMENTASI UU NOMOR 32 TAHUN 2009 TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP PADA KEGIATAN USAHA DI KABUPATEN PARIGI MOUTONG - Kaleb, Airin Vita Rustini (Katalogis, 2013)
Formulation of the problem in this study were: (1) how the implementation of Act Law No.32 of 2009 on â€œProtection and Enviromental Managementâ€ in business activities in the Parigi Moutong District ?, and (2) What factors are inhibiting the implementation of The Law Number 32/2009 â€œProtection and Enviromental Managementâ€ in the course of business in the District of Parigi Moutong ? This study method of instruction in quantitative descriptive analysis in the form of frequency table to solve research problems, using the theory refers to C. Edward III (1980:80) states that one of the approaches to the study of implementation should begin with the question of what is the prerequisite for the implementation of the policy and what is the major limiting factor for the success of policy implementation. Edward tries to answer two important questions to discuss four crucial variable in policy implementation, namely: 1) communication, 2) resources, 3) dispositions, and 4) bureaucratic structure. The results showed that the implementation of Law No.32 Year 2009 concerning the protection and management of environment on business activity in the District Parigi Moutong has been implemented with good views of the factor of communication, resources, disposition, and organizational structure.